Barriers and recommendations for a cervical cancer screening program among women in low-resource settings in Lagos Nigeria: a qualitative study - Tope Olubodun; Mobolanle Rasheedat Balogun; Abimbola Kofoworola Odeyemi; Oluwakemi Ololade Odukoya; Adedoyin Oyeyimika Ogunyemi; Oluchi Joan Kanma-Okafor; Ifeoma Peace Okafor; Ayodeji Bamidele Olubodun; Oluwatoyin Olanrewaju Progress Ogundele; Babatunde Ogunnowo; Akin Osibogun (figshare, 2022)
Abstract Background Cervical cancer is the fourth most common cancer in women globally despite being a largely treatable and preventable malignancy. Developing countries account for over 80% of all new cases. Women residing in low-resource settings such as those residing in slums have a higher risk of cervical cancer, and lower uptake of cervical cancer screening. Diverse barriers influence the uptake of cervical cancer screening among women in low-resource settings. Objectives This qualitative study was done prior to the introduction of a cervical cancer screening program in two slum areas in Lagos Nigeria and explored women’s knowledge about cervical cancer, and their perceived barriers and recommendations for the program. Method Four focus group discussions(FGD) were conducted among 35 women between the ages of 21–65 years residing in two urban slums in Lagos, Nigeria from February to April 2019. Each FGD was limited to 8–10 participants of women of similar ages. Voice recordings were transcribed verbatim and thematic analysis was done. Results Most of the women were not aware of cervical cancer and none knew the symptoms or risk factors of cervical cancer. The participants felt that the cervical cancer screening program would be well accepted in the community, however, expressed concerns about the cost of the screening test and the sex of the person performing the test. The recommendations proffered for a successful cervical cancer screening program include; reducing the cost of the test or providing the test free of charge, having people that speak the local language as part of the team, using female health care providers, using a private location within the community or nearby primary health center, and publicizing the program with the use of SMS, phone calls, town crier, and health talks. It was recommended that organizing health education sessions would help improve women’s poorly perceived susceptibility to cervical cancer. Conclusion Interventions to increase uptake of cervical cancer screening among women in low resource settings need to improve knowledge of cervical cancer and address barriers to cervical cancer screening such as cost, distance, and as much as possible, sex of the healthcare provider should be considered.
Keywords: Medicine; Physiology; Biotechnology; Cancer; 110309 Infectious Diseases